Identification of three novel mycoplasma species from ostriches in South Africa - Botes, A.; Peyrot, B.M.; Olivier, A.J.; Burger, W.P.; Bellstedt, D.U. (Veterinary microbiology, 2005)
Mycoplasmas have been implicated in certain clinical syndromes in ostriches and are associated with upper respiratory tract infections. As these infections result in production losses, they are of considerable economic importance to the South African ostrich industry. Although poultry mycoplasmas have been shown to infect ostriches, the existence of unique ostrich-specific mycoplasmas has been suggested. In this study, mycoplasmas were isolated from ostriches in the Klein Karoo, Central Karoo and Garden Route areas of the Western and Northern Cape Provinces of South Africa and identified using 16S rRNA gene sequencing. These sequences indicated that ostriches in these areas carry three unique mycoplasmas and were not infected with chicken mycoplasmas. Phylogenetic analysis of the 16S rRNA sequences of the three isolated ostrich mycoplasmas showed them to be quite divergent and to fall into two distinct phylogenetic groupings. Unique sequences within the 16S rRNA gene of the ostrich mycoplasmas were subsequently used for the development of specific primers for the detection and diagnosis of mycoplasma infections in ostriches. Chickens kept in close proximity to infected ostriches were not infected with these ostrich mycoplasmas.